PENERAPAN TEORI BEHAVIORISTIK MELALUI TEKNIK PRAKTEK DALAM MENINGKATKAN KEMAMPUAN SPEAKING SISWA PRIVATE INTELEGENSI MANDIRI - Supena, Fitriani Ramadhanti; Gumiandari, Septi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2021)
Learning activities are a means of acquiring new knowledge for anyone. Involving the active role of teachers and students. This study aims to dig deeper into Behavioristic Theory, especially in English lessons for Independent Private Intelligence students. Using practical methods and qualitative approaches, it is hoped that this research can provide a good discussion. The results of this study are: (a) knowing the development of Independent Private Intelligence students in memorizing English vocabulary and expressions given by the tutor, (b) knowing the effectiveness of Behavioristic Theory in the application of teaching and learning activities, and (c) knowing the suitability of one student with the other through the Behavioristic Theory approach. Keywords: English, Learning, Behaviorism.